Barriers and Facilitators for Implementing Paediatric Telemedicine: Rapid Review of User Perspectives - Tully, Louise; Case, Lucinda; Arthurs, Niamh; Sorensen, Jan; Marcin, James P.; O'Malley, Grace (Frontiers in Pediatrics, 2021)
Background: COVID-19 has brought to the fore an urgent need for secure information and communication technology (ICT) supported healthcare delivery, as the pertinence of infection control and social distancing continues. Telemedicine for paediatric care warrants special consideration around logistics, consent and assent, child welfare and communication that may differ to adult services. There is no systematic evidence synthesis available that outlines the implementation issues for incorporating telemedicine to paediatric services generally, or how users perceive these issues. Methods: We conducted a rapid mixed-methods evidence synthesis to identify barriers, facilitators, and documented stakeholder experiences of implementing paediatric telemedicine, to inform the pandemic response. A systematic search was undertaken by a research librarian in MEDLINE for relevant studies. All identified records were blind double-screened by two reviewers. Implementation-related data were extracted, and studies quality appraised using the Mixed-Methods Appraisal Tool. Qualitative findings were analysed thematically and then mapped to the Consolidated Framework for Implementation Research. Quantitative findings about barriers and facilitators for implementation were narratively synthesised. Results: We identified 27 eligible studies (19 quantitative; 5 mixed-methods, 3 qualitative). Important challenges highlighted from the perspective of the healthcare providers included issues with ICT proficiency, lack of confidence in the quality/reliability of the technology, connectivity issues, concerns around legal issues, increased administrative burden and/or fear of inability to conduct thorough examinations with reliance on subjective descriptions. Facilitators included clear dissemination of the aims of ICT services, involvement of staff throughout planning and implementation, sufficient training, and cultivation of telemedicine champions. Families often expressed preference for in-person visits but those who had tried tele-consultations, lived far from clinics, or perceived increased convenience with technology considered telemedicine more favourably. Concerns from parents included the responsibility of describing their child’s condition in the absence of an in-person examination. Discussion: Healthcare providers and families who have experienced tele-consultations generally report high satisfaction and usability for such services. The use of ICT to facilitate paediatric healthcare consultations is feasible for certain clinical encounters and can work well with appropriate planning and quality facilities in place.